Effect of financial stress on self-rereported health and quality of life among older adults in five developing countries: a cross sectional analysis of WHO-SAGE survey - Rui Huang (BMC Geriatrics, 2020)
Abstract In developing countries, older adults (65 years of age and above) share an increased vulnerability to catastrophic health expenditures and financial stress which can have significant bearing on their health and well-being. Currently, research evidence on how financial stress correlates with health and well-being among older adults in the developing countries is limited. Therefore, in this study, we aimed to assess the relationship between financial stress and subjective 1) health, 2) depression, 3) quality of life, and 4) life satisfaction among older adults in five developing countries. Methods Data used in this study were cross-sectional which were collected from the first wave of Study on Global AGEing and Health (SAGE) survey of World Health Organization. Sample population were 12,299 community dwelling men and women in China (n = 4548), Ghana (n = 1968), India (n = 2441), South Africa (n = 1924), and Russia (n = 1418). Using generalized linear models with logit links, we assessed the correlation between self-reported financial stress and income inequality with the four outcome measures by adjusting for various sociodemographic factors. Results Overall, the prevalence of good self-reported health, quality of life and positive life-satisfaction was 47.11, 79.25 and 44.40% respectively, while 20.13% of the participants reported having depression during past 12 months. Only about a fifth (18.67%) of the participants reported having enough money to meet daily their necessities completely, while more than quarter (28.45%) were in the lowest income quintile. With a few exceptions, the odds of reporting good self-reported health, quality of life, and life satisfaction were generally lower among those with varying degrees of financial stress, and larger among those in the higher income quintiles. Conversely, the likelihood of self-reported depression was significantly higher among those with any level of financial stress, and lower among those in the higher income quintiles. Conclusion This study concludes that both subjectively and objectively measured financial stress are inversely associated with good self-reported health, quality of life, life satisfaction, and positively associated with self-reported depression among older adults.